NATION AND NATIONALISM – THE ORIGIN OF THE TERM AND HISTORY OF THE IDEA - Bodrožić, Đuro (National interest, 2023)
In order to know the nature of an ideal, it is necessary to know its origin and historical development – intellectual and social. Nationality is a cultural phenomenon, it is not tied to ideologies but to the cultural systems within which it arose and against which it arose. And these are, first of all, Roman Catholic universalism and dynastic kingdom. The initial meaning of the term nation is not as we understand it in our time. Today's meaning of this term is associated with the French Revolution – a people under one government that knows itself in its own state. The greatest change brought about by the Napoleonic wars in domain of warfare was not military but political. A subject of the old regime became a citizen, he had the obligation to serve his military service and to fight if the nation asked for it. It was a change of the first order not only of military structures, it was about the birth of a nation and a national state. A nation is a people that knows itself in its state, and the state does not bow down. And that is why it could be said that a nation is a people who are ready to die and kill for the idea of their homeland. And a nation-state is a state that entrusts its destiny to the hands of a conscripted army, fearing neither rebellion nor desertion.
Keywords: nation; national identity; nation state; people's army; Treaty of Westphalia; French Revolution; Roman Catholic Church; dynastic kingdom